Vegetation syntaxonomy of seaside-dune’s ecosystems of Ukraine. Cakiletea maritimae and Ammophiletea classes (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Authors elucidates the problems of syntaxonomy of Cakiletea maritimae and Ammophiletea in Europe. A comparative characteristics and classification of syntaxa mentioned are given.
Keywords: vegetation, Cakiletea maritimae, Ammophiletea, syntaxonomy.